Clustering Of Polyelectrolyte Coated Magnetic Nanoparticles Under Repetitive Cycle Of Magnetization - Zulkifli, Muhammad Azwar Hafify (Universiti Sains Malaysia, 2018)
The sample of naked iron oxide nanoparticles (IONPs) was prepared and been functionalized by using poly (diallyldimethylammonium chloride) (PDDA) electrolyte as a coating agent in order to improve the colloidal stability of the IONPs in the suspension. The presence of PDDA as an adlayer adsorbed on IONPs introduced electrosteric stabilization towards particles in suspension, thus suppressed the van der Waals attraction and magnetic dipole-dipole interaction force between particles reducing particles aggregation. Characterization of naked IONPs and functionalized IONPs been conducted by using dynamic light scattering (DLS) for particles size and zeta potential measurement. The characterization to ensure the successful coating of IONPs with PDDA macromolecules. The IONPs samples are prepared into 3 different concentration (50, 100 and 500 ppm) to conduct the study on effect of repetitive exposure of IONPs sample towards magnetic field. The major focuses would be the effect on the cluster size formed and colloidal stability of particles suspension after been subjected to repetitive magnetization. The magnetization cycle of IONPs samples was started from 1 cycle followed by 3 and 5 magnetization cycles. For cluster size formed, as going up the magnetization cycle there was not much different can be seen from the particles size measurement by DLS for all concentrations. The same thing goes to study on colloidal stability of particles been conducted through kinetic study by UV-Vis spectrophotometer, measuring the absorbance of IONPs sample. The decay rate for normalized absorbance was almost the same for all magnetization cycles and concentrations that proving the repetitive magnetization has relatively insignificant effect towards particles stability in suspension.